Challenges on detection, identification and monitoring of indoor airborne chemical-biological agents. (September 2020) - Karakitsios, Spyros; Busker, Ruud; Tjärnhage, Torbjorn; Armand, Patrick; Dybwad, Marius; Nielsen, Merete Folmer; Burman, Jan; Burke, James; Brinek, Josef; Bartzis, John; Maggos, Thomas; Theocharidou, Marianthi; et al.
Graphical abstract: Highlights: Define relevant scenarios of indoor airborne threats. Simulation potential events. Optimal setup of sensoring. Abstract: Potential chemical and biological (CB) attacks in indoor spaces pose specific challenges for prevention and preparedness. This paper summarises the conclusions obtained from the work conducted in the framework of the ERNCIP 1 . A thorough review of the existing and emerging technologies for CB detection, coupled with simulations of CB airborne dispersion in (critical) infrastructures to investigate the implementation of such sensors is presented. The conclusions include: (a) limitations of current sensor technology, (b) the effect of spatial variability of contamination within a building envelop on the effectiveness of such technology (c) the importance of early identification of both CB compounds for post-event mitigation.